دور المسؤولية الاجتماعية في تحسين تنافسية المؤسسات الاقتصادية - علالي, مليكة (Recherches économiques et managériales, 2018)
تعد المسؤولية الاجتماعية بمثابة مبادرات اختيارية تقوم بها المؤسسات وهي صورة من صور الملائمة الاجتماعية الواجبة عليها عبر تجسيد دورها الاجتماعي والأخلاقي في حماية البيئة، المجتمع وجميع الأطراف المتعاملة معها،وتأتي هذه الدراسة لإبراز دور المسؤولية الاجتماعية في تحسين تنافسية المؤسسات الاقتصادية من خلال التأصيل النظري لكل من المسؤولية الاجتماعية والتنافسية وما يرتبط بها من مصطلحات منافسة،ميزة تنافسية، ... ، وتمثلت نتائج الدراسة في إثبات دور المسؤولية الاجتماعية في تحسين تنافسية المؤسسات من خلال تحسين العلاقة مع أصحاب المصالح ،ودور تبني المسؤولية الاجتماعية من طرف المؤسسة في تحسين سمعتها وتحقيق مزايا تنافسية تمكنها من تحسين تنافسيتها في السوق،وتم تدعيم هذه النتائج بأمثلة واقعية لمؤسسات عالمية رائدة في المسؤولية الاجتماعية . الكلمات المفتاحية : المسؤولية الاجتماعية، التنافسية، المنافسة، الميزة التنافسية، المؤسسات الاقتصادية . Abstract Social responsibility is an optional initiative of the institutions, a form of social suitability, through the embodiment of its social and moral role in the protection of the environment, the society and all parties involved. This study highlights the role of social responsibility in improving the competitive of economic institutions through the conceptualization of both Social responsibility, competitive and associated terms , Competition, competitive advantage.., The results of the study were to demonstrate the role of social responsibility in improving the competitive of institutions by improving the relationship with stakeholders, the role of adoption Social responsibility by the institution to improve its reputation and achieve competitive advantages to improve its competitive in the market, and these results were supported by realistic examples of leading institutions in social responsibility. Keywords : Social responsibility, Competition, Competitive advantage, Competitive, Economic institutions.